DINAMIKA SPASIAL PERKEMBANGAN MINIMARKET DI KORIDOR JALAN KALIURANG - , ALPEUS MANIHURUK ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Various surveys and studies in Indonesia and abroad shows that the minimarket is ritail who have highest rate of expansion and agresivitation compared to all kinds of modern ritail there because not only can be found in urban areas, but also in suburban and even rural areas. The existence of this minimarket gives a certain pattern and trends that are spatially and temporally can be measured and mapped. Formed spatial dynamics will also show different associations to geography factors such as the level of the urban, count of population, service hierarchy, and accessibility heirarchy about to selection and placement of outlets location so that this research with title âthe spatial dynamics of minimarket development in Koridor Jalan Kaliurangâ is important and interesting to do with goals: 1) identify the spatial dynamics of minimarket development, 2) describe the geographic factors associated with spatial dynamics of minimarket, and 3) identify the location of the minimarket development direction of the policy implications of the new minimarket. The research method used is a combination of quantitative-qualitative methods with techniques of trend analysis (to examine the temporal dynamics of the trend), and nearest neighbourhood (minimarket spatial pattern analysis) on the first goal. The second goals use Getis Ord G analysis method (high-low cluster study related to the prefrence of location) and descriptive statistics (frequency tables), while the third used image analysis methods (landing site of new development minimarket). The results found that the spatial dynamics of minimarket development in Koridor Jalan Kaliurang is forming diffuse pattern in the early period of its existence (2003-2008), clustered in the middle period (2009-2010), and re-spread in recent years period (2011-2012). Spatial distribution pattern is related to the potential economy, regulatory dynamics of the region, and also the availability of space. While geographical factors have asociate with the selection and placement location of preference minimarket in Koridor Jalan Kaliurang is urbanity and population factors. This is because both of the geographical factors encourage high population activities thus providing considerable economic potential. For the development of new minimarket site directed at locations that have not yet had a minimarket are the urban hierarchy and the large population resulting in the distribution of the number of service facilities in the Desa Sinduharjo (two locations), Sardonoharjo (one location, and Sinduadi (one location).